Proposal for a National Bank of non-prosecution agreements - Rhenius Nitzke, Felipe; Cândido, Ana Clara (Advanced Notes in Information Science, 2023)
The complexity of the modern world, with the advance of Information and Communications Technologies, has brought to light a new area of human knowledge, the so-called Digital Humanities. Despite the many difficulties of conceptualization, in synthesis, Digital Humanities introduces digital technologies applied to Humanities courses. Digital Humanities can be used within the scope of the Anti-Crime Package (Law nº 13,964/2019), specifically in Non-Prosecution Agreements. The absence of communication channels between the 29 Public Prosecution Offices that can sign such agreements prevents verifying individuals who have already signed them. Thus, one of the legal requirements of this measure cannot be guaranteed. This article aims to propose a National Bank of Non-Prosecution Agreements within the scope of Digital Humanities and Knowledge Organization for consultation purposes by the agencies involved and the general population, an initiative to be coordinated by the National Council of the Public Prosecution Service.